STRATEGI PROMOSI PANTAI JAI JAI RAOK DESA PADANG TANGGUNG KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - M. Iqbal Fadillah; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Promotion is a way of communicating that is usually done in an organization that has the goal of attracting potential buyers to buy the goods and services being sold or offered. This study aims to determine the promotion strategy for Bumdes Pantai Jai Jai Raok, Padang Kemerdekaan Village, Pangean District, Kuantan Singingi Regency. This study used a qualitative method with a descriptive approach, the subject of this study was the Head of Padangnggung Village, Kuantan Singingi Regency, Secretary of the Rajo Bujang Village-Owned Enterprise (BUMDes), Kuantan Singingi Regency. Data collection is done by interviews, observation, and documentation. Data analysis carried out in this study was data reduction, data presentation, and drawing conclusions. The results of this study are that the promotion is carried out through 3 (three) techniques which include Advertising, Sales Promotion, Public Relations. However, until now the results are still not good because there are still many promotions that have not been carried out and have not made maximum use of promotional media. maximally available. Keywords: tourism promotion, promotion technique, jai-jai raok beach